'A polyphonic tale': Arendt, Cavarero and storytelling in Sarah Polley's Stories We Tell (2012). Issue 1 (1st June 2021) - Angeli, Silvia
This article proposes a reading of Sarah Polley's Stories We Tell (2012) through the work of Hannah Arendt and Adriana Cavarero. Far from being a simple homage to her late mother Diane, Polley's film is a 'polyphonic tale', a complex and multi-layered narrative which allows for an exploration of the many functions of (cinematic) storytelling. Highlighting the close link between relating narratives and personal identity, the film sheds light on both the innate desire for biography that characterizes us as human beings and the complex and dynamic relationship between storytellers and listeners. The way we tell stories affects the narrator(s), their audience and the fabric of the story itself in a process that ensures both continuity and change. Referring to Arendt's notion of political storytelling, I conclude by suggesting that Stories We Tell, like the Greek polis, functions as an 'organized remembrance', a community whose purpose is to preserve fragile human deeds and words from oblivion.